The perceptions of professional nurses regarding factors affecting the provision of quality health care services at selected rural public clinics in the Capricorn district, Limpopo Province - Nick T. Matlala; Rambelani N. Malema; Mamare A. Bopape; Peter M. Mphekgwana (AOSIS, 2021)
Background: Despite many initiatives made by the National Department of Health through the Minister of Health, the provision of quality health care services remains a serious challenge in South Africa, especially in public rural clinics. Aim: The study aims to determine the perceptions of professional nurses on the factors affecting the provision of quality health care services at selected public primary health care clinics in rural areas of the Capricorn District, Limpopo Province. Setting: The study was conducted at selected public primary health care clinics in rural areas of the Capricorn District, Limpopo Province. Methods: This study utilised a quantitative method, descriptive and a cross-sectional study conducted for three months at the selected public primary health care clinics. A structured self-administered questionnaire was used to collect data from 155 professional nurses who met the selection criteria. Data were analysed using Statistical Package for Social Sciences programme version 26.0. Results: The results of 155 professional nurses were only 116 (74%) and reported that the use of modern technology such as electronic blood pressure, sonar machines and pulse reading computers improves the quality of health care services. Also 129 (84%), 124 (77%) and 118 (76%) reported that they were overwhelmed by the workload, the staff attitude and cleanliness of the clinic, respectively, which all affect the quality of health care services rendered. Moreover, only about 29 (19%) were satisfied with the salary they earned. Conclusion: Despite the effort and interventions put in place by the Department of Health with regard to the Ideal Clinic Realisation and Maintenance in response to the current deficiencies in the quality of primary health care services and to lay a strong foundation for the implementation of National Health Insurance. The quality of health care services is still hindered by several factors such as an overwhelming workload, the attitude of the staff and cleanliness in the work environment, poor infrastructure and the professional nurses perceive the environment as lacking equipment.